In vitro combined effect of Doxorubicin and sulfonated zinc Phthalocyanine–mediated photodynamic therapy on MCF-7 breast cancer cells - Eric Chekwube Aniogo; Blassan Plackal Adimuriyil George; Heidi Abrahamse (Tumor Biology)
Doxorubicin is a broad-spectrum antibiotic and anticancer drug used to treat a variety of human malignancies like breast cancer and leukaemia. Unfortunately, a dose-dependent side effect of this drug is common, representing a major obstacle to its use despite its therapeutic efficacy. Photodynamic therapy is an emerging non-invasive potential adjuvant for conventional cancer treatment. In an attempt to circumvent the dose-limiting effect of doxorubicin, this study aimed to investigate cellular anticancer activity of doxorubicin and sulfonated zinc phthalocyanine–mediated photodynamic therapy on MCF-7 cells alone and in combination. Furthermore, we investigated the cell death pathway resulting from the combination treatment. MCF-7 cells were incubated with 0.5 µM concentration of doxorubicin for 20 h, afterwards, various concentrations of sulfonated zinc phthalocyanine were added and incubated for 4 h. Cells were irradiated using a 681.5 nm diode laser at 4.53 mW/cm 2 for 18 min 24 s (5 J/cm 2 ). Cell viability and proliferation were measured using trypan blue assay and homogeneous adenosine triphosphate quantitation assay, respectively, while qualitative changes in cellular morphology were observed under inverted light microscopy. Cellular DNA damage was assessed under fluorescent microscopy and Annexin V/propidium iodide stain was used to investigate the cell death pathway. Findings from this study shown that combined treatment with doxorubicin and photodynamic therapy was more effective in inhibiting the proliferation and growth of MCF-7 cells. Overall, the results indicate that combination of smaller dose of doxorubicin with photodynamic therapy is a promising combined treatment strategy for breast carcinoma. However, this combination warrants further investigation.